CONNECTIVITY RELATIONSHIP OF FLUID FLOW ON DEFORMATION BAND: ANALOG STUDY AT PETANI FORMATION, RIAU, INDONESIA - Choanji, Tiggi; Rita, Novia; Yuskar, Yuniarti; Pradana, Aulia (Fakultas Teknik Geologi Universitas Padjadjaran, 2017)
Deformation band at Petani Formation was a type of disaggregation band, where deformation resulted from tectonics stress at Plio – Pleistocene affecting sandstone layer that being deformed and resulted strain localization feature, filling with iron oxide sand. Aim of this study was to analyze effect of fluid flow connectitvity on layer that having deformation band. The study area was located at Tapung Hulu and Batubelah, Kampar, Riau. The method for this research was using grain size analysis, distribution analysis of shear trends, and measurement of permeability for each deformation band. Result shows that grains size dominantly fine sand – medium sand (0.149 mm – 0.297 mm), followed by the distribution of deformation trends showing NW – SE direction, and good in permeability (3.4 mD– 188.4mD). It can be concluded that the tectonic which create structural features of deformation band can create good permeability for fluid flow.Keywords : Deformation Band, Fluid Flow, Tapung Hulu, Batu Belah, Permeability